Law and Innovation of Productive Waqf Management to Support the Sustainable Development Goals (SDGs) - Saprida; Meriyati; Muharir; Anuar Puadi; Dandy Okorontah (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: The objective of this study is to analyze the legal and innovative aspects of productive waqf management and explore its role in promoting the achievement of Sustainable Development Goals (SDGs). By examining the framework and implementation of productive waqf, this research seeks to understand its potential impact on economic, educational, and environmental outcomes. Theoretical framework: The study is based on Islamic law, specifically Law No. 41 of 2004 on Waqf and Government Regulation No. 42 of 2006 (amended in 2018). It also draws from the Compilation of Islamic Law (KHI), focusing on the management of productive waqf for investment and service production. Literature review: The review examines existing research on productive waqf's legal framework and its potential impact on SDGs, especially in sectors like MSMEs, education, and the environment. Methods: A qualitative approach is used, utilizing a literature review to collect and analyze data from relevant legal texts and academic sources. Results: The study finds that productive waqf in Indonesia is governed by specific laws and has significant potential to support SDGs. It can empower MSMEs, contribute to education, and promote sustainable environmental practices. Implications: The findings suggest that productive waqf can be a key tool in advancing SDGs, particularly in economic development, education, and environmental sustainability. Novelty: This research highlights the innovative role of productive waqf in achieving SDGs, focusing on sustainable practices like eco-friendly agriculture and renewable energy, areas not extensively explored in previous studies.